QUANTITATIVE STUDIES OF THE IMMUNOGLOBULIN SEQUENCE IN THE RESPONSE OF THE RABBIT TO A SOMATIC ANTIGEN - Altemeier, W. A. (The Rockefeller University Press, 1966)
Employing a sensitive and immunoglobulin-specific assay method based upon antiglobulin augmentation, quantitative and qualitative aspects of the primary and secondary response of the rabbit to Salmonella typhimurium O antigens have been evaluated. These studies examine the validity of the method of assay for detecting and measuring γG- and γM-antibodies produced in response to whole organisms or its lipopolysaccharide. The results show that during the primary response γG-antibodies, not detectable by usual techniques, are produced in a pattern similar to that reported in animals stimulated by other classes of antigens. Moreover, the γG response following reinjection is characteristic of a secondary-type response. In contrast, γM-antibody levels after both primary and secondary stimulation rose equally to levels between 1 and 4 mg/ml. Despite increased sensitivity of detection and quantitative estimates of the actual molar concentration of each immunoglobulin, the minimal interval between γM and γG appearance in serum was not less than 1.5 days. The variable degree of augmentation of agglutination by antiglobulin reagent found during the immune response severely limits the quantitative usefulness of the methods developed. However, the data suggest that qualitative changes in anti-O antibodies interpretable as changes in avidity occur regularly during the immune response.